EVALUATION OF PROJECT IMPLEMENTATION PERFORMANCE WITH EARNED VALUE METHODS - Made Sudiarsa; I Gede Sastra Wibawa; I Ketut Sutapa (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Planning and controlling the execution of a project is part of the overall construction project management. In addition to assessment in terms of quality, achievement of a project can be assessed in terms of cost and time. Earned value method is the integrated cost control and project schedule. This method provides project performance status information in terms of cost and time in the project reporting period. In evaluating the performance of the development project of Villa Shimamoto Ryosaku, the performance of the cost aspect shows the savings from the plan, This is shown from the value Cost Performance Index (CPI) > 1 On monthly reporting3 = 1.39, the monthly 6 = 1.97, and the monthly 11 = 1.73 While the performance of the schedule aspect shows the delay of the plan, this is shown from the value Schedule Performance Index (SPI) < 1 on monthly reporting 3= 0.79,the monthly 6 = 0.93, and the monthly 11 = 0.94. Estimate Temporary Cost (ETC) is Rp 480,175,422.16, and Estimation At Completion (EAS) is Rp2,026,445,457.16, while Budgeted At Completion (BAC) is Rp3,502,000,000.00 so get Variance at Compeltioan (VAC) is Rp1,409,621,615.49 and Estimation Temporary Schedule (ETS) is 3.2 month, and Estimation At Schedul (EAS) is 14.2 Month while the time specified in the contract during 14 month, So the project is delayed during 0.2 month (1 week).